2017
DOI: 10.3892/ol.2017.5855
|View full text |Cite
|
Sign up to set email alerts
|

T-box 3 overexpression is associated with poor prognosis of non-small cell lung cancer

Abstract: Abstract. T-box 3 (Tbx3), a member of the T-box transcription factor family, serves a crucial role in embryonic development and cancer progression. Previous studies have demonstrated the clinical significance of Tbx3 in numerous types of cancer. However, the expression level and pathological function of Tbx3 in non-small cell lung cancer (NSCLC) are unknown. To the best of our knowledge, the present study provided the first evidence demonstrating the clinicopathological significance of Tbx3 in NSCLC. Tbx3 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
(30 reference statements)
1
4
0
Order By: Relevance
“…As HYAL1 was reported to have no effect on p53-mediated cell death [26], our finding suggests a novel and indirect association between HYAL1 and p53 through DACH1 regulation. TRIM24, TBX3, and KHDRBS1 were upregulated in lung cancer [44][45][46]. Hence, we noted their significant downregulation in HYAL1-overexpressed HFL-1 cells, which is consistent with their role in inducing fibroproliferation.…”
supporting
confidence: 84%
“…As HYAL1 was reported to have no effect on p53-mediated cell death [26], our finding suggests a novel and indirect association between HYAL1 and p53 through DACH1 regulation. TRIM24, TBX3, and KHDRBS1 were upregulated in lung cancer [44][45][46]. Hence, we noted their significant downregulation in HYAL1-overexpressed HFL-1 cells, which is consistent with their role in inducing fibroproliferation.…”
supporting
confidence: 84%
“…Our findings on suppressed expression of TBX2 subfamily in NSCLC are also in congruence with various recent reports implicating tumor suppressive properties for members of the TBX2 subfamily. While the report by Wu et al [ 41 ] showed that TBX3 is up-regulated in NSCLC, the same study demonstrated that a fraction of NSCLCs show reduced expression of the gene. Low expression of TBX4 gene was reported to be associated with worse prognosis among patients with stage II pancreatic ductal adenocarcinoma [ 48 ].…”
Section: Discussionmentioning
confidence: 91%
“…by quantitative real-time PCR) in NSCLCs and paired normal lung tissues in a smaller subset of NSCLC cases ( n = 40 to 50) [ 39 , 40 ] demonstrating that the gene is elevated in the tumors. These earlier studies [ 39 41 ], albeit few, point to putative oncogenic roles and properties for the TBX2 gene in human NSCLC. In contrast, our findings, collectively, revealed that the TBX2 gene is markedly suppressed in NSCLC relative to normal lung from four publicly available expression datasets [ 23 26 ] ( Supplementary Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…EGFR -amp demonstrated a much higher rate in paired CSF samples (8/22, 36%) than in the PLA samples (1/22, 5%). Overexpression of TBX3 is uniquely associated with tumor size, and inactivation of PTEN is notably associated with poor survival in NSCLC patients [ 11 , 12 ]. The detection rates of TBX3 and PTEN in CSF were almost double those of the paired PLA samples ( Figure 3 C), making the liquid CSF medium an ideal candidate for categorizing patients treated with EGFR -TKI.…”
Section: Resultsmentioning
confidence: 99%